A STUDY ON INTERNAL CONTROLS AND AUDIT TRAIL IN TALLY ERP - Porwal, Raj; Damodaran, Deepa; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
In modern accounting environments, internal controls and audit trail mechanisms have become essential components for ensuring transparency, accuracy, and reliability of financial information. With the increasing digitalisation of accounting systems, software such as Tally ERP has emerged as a leading platform offering built-in internal control features designed to reduce errors, prevent fraud, and improve efficiency. This research paper explores the significance, structure, and functioning of internal controls within Tally ERP, with a special focus on the audit trail feature. The purpose of this study is to understand how internal controls integrated into Tally ERP enhance data security, support compliance, and strengthen financial reporting systems. The research evaluates existing literature, analyses the components of internal controls, and examines the impact of audit trail features such as user log tracking, voucher change history, timestamped modifications, access restrictions, and approval workflows. The study also reviews common financial errors, reasons behind them, and how audit trails assist in early detection. Findings reveal that Tally ERP’s internal control framework, when implemented effectively, helps reduce manual errors, ensures verification at multiple levels, restricts unauthorized data alterations, and improves audit readiness. Finally, the paper provides recommendations for improving the efficiency of internal control systems, including user training, automation of validations, strengthening access rights, and scheduling regular audit trail reviews. This research highlights the growing need for digital reliability in financial processes and positions Tally ERP as a strong tool for ensuring accountability in financial transactions.